2005
DOI: 10.1371/journal.pgen.0030163.eor
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Patterns of Nucleotide Polymorphism in Domesticated Rice

Abstract: Domesticated Asian rice (Oryza sativa) is one of the oldest domesticated crop species in the world, having fed more people than any other plant in human history. We report the patterns of DNA sequence variation in rice and its wild ancestor, O. rufipogon, across 111 randomly chosen gene fragments, and use these to infer the evolutionary dynamics that led to the origins of rice. There is a genome-wide excess of high-frequency derived single nucleotide polymorphisms (SNPs) in O. sativa varieties, a pattern that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
259
6
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(295 citation statements)
references
References 32 publications
(41 reference statements)
29
259
6
1
Order By: Relevance
“…5b (Caicedo et al 2007). In addition, too many loci had SNPs that were at a high frequency in O. sativa.…”
Section: The Species O Sativamentioning
confidence: 98%
“…5b (Caicedo et al 2007). In addition, too many loci had SNPs that were at a high frequency in O. sativa.…”
Section: The Species O Sativamentioning
confidence: 98%
“…The genetic diversity of cultivated rice germplasm on a global scale has been well characterized using molecular markers (Caicedo et al 2007;Garris et al 2005;Glaszmann 1987;Yang et al 1994;Yu et al 2003). To encompass the entire range of rice diversity, these studies have sampled rice varieties from many different rice-growing countries around the world.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the accelerated evolution provided by intense artificial selection and seed exchanges among local farmers has led to dramatic changes in the genetics of cultivated crops in a relatively short time frame (<10,000 years). While the story of rice domestication is still being unraveled based on interpretations of geographic and phylogenetic data (Caicedo et al 2007;Londo et al 2006) and analysis of cloned domestication genes (Kovach et al 2007;), it appears that rice was domesticated from diverse gene pools and that gene flow among sub-populations and with wild ancestral populations has created a complex series of events leading to the modern day fabric of rice diversity (Sang and Ge 2007;Sweeney and McCouch 2007), although the possibility of a single domestication event is still debated (Gao and Innan 2008;Vaughan et al 2008). While the relationships between the earliest domesticates and indigenous landraces surviving in rice-growing regions today are still unclear, signatures of shared ancestry, selection, and introgression are written in the genomes of traditional varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that rice is a major cereal and a model system for plant biology, the evolutionary origins and domestication processes of cultivated rice have long been debated. The puzzles about rice domestication include: (1) where the geographic origin of cultivated rice was, (2) which types of O. rufipogon served as its direct wild progenitor, and (3) whether the two subspecies of cultivated rice, indica and japonica, are derived from a single or multiple domestications.A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%
“…A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%